Prognostic factors affecting the outcome after allogeneic haematopoietic stem cell transplantation for myelodysplastic syndrome - Belohlavkova, P; Vrbacky, F; Smolej, L; Radocha, J; Lanska, M; Visek, B; Kupsa, T; Zavrelova, A; Zak, P (Leukemia research reports, 2021)
In the present study, we retrospectively analysed the results of HSCT in 47 consecutive patients with MDS diagnosed at our department between 2002 and 2019, with a focus on possible predictive factors influencing overall survival (OS), the development of relapse, infections, and the occurrence of graft versus host disease (GvHD). In a univariate analysis, the pre-transplantation value of blasts in the marrow < 5% (p = 0.006), the revised International Prognostic Scoring System (IPSS-R) (p = 0.041), and karyotype (p = 0.009) were predictive of OS. Neither the elevation of serum ferritin (> 1000 ug/ml) nor increased C-reactive protein (CRP) (> 5 mg/l) was associated with shorter OS. In contrast, elevated serum lactate dehydrogenase (LDH) (> 213 U/l) was associated with shorter OS (p = 0.04).
Keywords: Allogeneic haematopoietic stem-cell transplantation; Myelodysplastic syndrome; Prognostic factors